Electronic Land Certificates: A Breakthrough in Digital Transformation or a New Challenge to Legal Certainty - Basir, Mustofa Abdul; Utami, Pipit Saputri; Wahanisa, Rofi; Suhadi, Suhadi (Pandecta Research Law Journal, 2026)
Digital transformation in the legal sector has become inevitable, including in Indonesia’s agrarian governance system through the implementation of electronic land certificates. Nevertheless, the transition from conventional land certificates to digital documents also generates challenges related to legal certainty and public trust toward digital governance. This article aims to analyze whether electronic land certificates represent a genuine digital breakthrough or instead create new legal and social vulnerabilities. This study employs a qualitative approach through analytical methods and secondary data observation. The findings demonstrate that the success of electronic land certificates is not solely determined by technological sophistication, but also by regulatory readiness, institutional accountability, cybersecurity protection, and the level of public digital literacy. The study further reveals that community resistance and fearfulness remain significant due to concerns regarding cyberattacks, misuse of personal data, inequality in digital infrastructure, and the declining symbolic legitimacy of physical land certificates within agrarian culture. This study suggest that the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) strengthen transparent governance mechanisms, improve public participation, and establish adaptive legal standards concerning digital evidence and electronic land administration. In addition, the Ministry of Communication and Digital Affairs should reinforce cybersecurity infrastructure, expand equitable internet access, and formulate stronger personal data protection frameworks to ensure that the digital transformation of Indonesia’s land system remains legally secure, socially accepted, and institutionally sustainable.